2020
DOI: 10.18203/2319-2003.ijbcp20202185
|View full text |Cite
|
Sign up to set email alerts
|

Drug utilization study of antipsychotics among schizophrenia patients in a tertiary care teaching hospital: a retrospective observational study

Abstract: Background: Aim of the study was to evaluate the drug utilization pattern of antipsychotics in schizophrenia patients in a tertiary care hospital.Methods: A retrospective observational study was conducted over a period of one year. Demographic data and drug utilization pattern of antipsychotics was collected from the surveyed prescriptions. Using WHO prescribing indicators data was analysed. Results were expressed in percentage.Results: Out of 300 prescriptions analysed, males were 58% and females 42%. Majorit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 10 publications
1
1
0
Order By: Relevance
“…As similar to the trend seen in other studies, olanzapine (n=26) followed by haloperidol (n=15) and risperidone (n=15) were the most commonly prescribed antipsychotics among the study populations. 10,13,25,26 In the present study, only one prescription of clozapine (n=1) has reported which was similar to the previous studies that reported a lower rate of prescription of clozapine. 13,15,27 Majority of the patients with bipolar disorder were prescribed with mood stabilizers and sodium valproate (n=21) is the most commonly prescribed anti-mania medication as compared to lithium (n=4) in the present study.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…As similar to the trend seen in other studies, olanzapine (n=26) followed by haloperidol (n=15) and risperidone (n=15) were the most commonly prescribed antipsychotics among the study populations. 10,13,25,26 In the present study, only one prescription of clozapine (n=1) has reported which was similar to the previous studies that reported a lower rate of prescription of clozapine. 13,15,27 Majority of the patients with bipolar disorder were prescribed with mood stabilizers and sodium valproate (n=21) is the most commonly prescribed anti-mania medication as compared to lithium (n=4) in the present study.…”
Section: Discussionsupporting
confidence: 90%
“…This finding is higher than that found in similar studies where it ranged from 0.03-6.2% . 11,13,17,25 Haloperidol (40.74%) is the most commonly used parenteral depot preparations in our study. Our findings are in line with the studies examining the use of psychotropic medications in schizophrenia patients in other countries.…”
Section: Discussionmentioning
confidence: 84%